2013
DOI: 10.1017/gov.2013.1
|View full text |Cite
|
Sign up to set email alerts
|

The Cabinet: A Viable Definition and its Composition in View of a Comparative Analysis

Abstract: This article is made up of two main parts. The first part points out two different definitions of cabinet – that is, functional and legal definitions. It also highlights the strong points and the shortcomings of both, proposing at the same time a new definition more suitable for a comparative analysis. In doing this, it puts forward some useful criteria with a view to establishing what a minister actually is, what a cabinet is and how it is made up. The second part provides an overview of the structures of gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…The main distinction is between internal arenas (where only government members participate), mixed arenas (both internal and external actors), and external arenas (only nongovernment members). Internal actors are both senior and junior ministers (together with their personal advisers); civil servants are instead external (Barbieri and Vercesi ). However, all the arenas considered are internal with respect to the coalition and therefore arenas, such as parliamentary arenas—where members of the opposition attend—are excluded.…”
Section: The Process Of Inter‐party Conflict Management: Who Participmentioning
confidence: 99%
“…The main distinction is between internal arenas (where only government members participate), mixed arenas (both internal and external actors), and external arenas (only nongovernment members). Internal actors are both senior and junior ministers (together with their personal advisers); civil servants are instead external (Barbieri and Vercesi ). However, all the arenas considered are internal with respect to the coalition and therefore arenas, such as parliamentary arenas—where members of the opposition attend—are excluded.…”
Section: The Process Of Inter‐party Conflict Management: Who Participmentioning
confidence: 99%
“…This is important not only for operational purposes, but because it sets a threshold for determining who actually has the ability to affect spending decisions. One recent study suggests that relying on function to operationalize a definition can present more complications than departing from a legal, institutional understanding (Barbieri and Vercesi 2013). A standard approach is to count only officials with full ministerial rank, thus excluding deputy ministers, secretaries of state, regional ministers or other officials who would add even more to these numbers (van de Walle 2001).…”
Section: Are Africa’s Cabinets Cumbersome?mentioning
confidence: 99%
“…Several studies of prime ministers (e.g. Jones 1991;Pasquino 2005b;Poguntke and Webb 2007) have shown that, of the party-related factors, leadership of the coalition and party leadership (Barbieri and Vercesi 2013) are more crucial resources than others. For this reason, I have mainly focused on them, and the remainder of the article is based on this theoretical premise.…”
Section: The Theoretical Premisementioning
confidence: 99%